Lean Tissue Mass Wasting is Associated With Increased Risk of Mortality Among Women With Pulmonary Tuberculosis in Urban Uganda - Mupere, Ezekiel; Malone, Lashaunda; Zalwango, Sarah; Chiunda, Allan; Okwera, Alphonse; Parraga, Isabel; Stein, Catherine M.; Tisch, Daniel J.; Mugerwa, Roy; Boom, W. Henry; Mayanja, Harriet; Whalen, Christopher C. (Elsevier Inc., 2012)
OBJECTIVES: We assessed the impact of wasting on survival in patients with tuberculosis by using a precise height-normalized lean tissue mass index (LMI) estimated by bioelectrical impedance analysis and body mass index (BMI). METHODS: In a retrospective cohort study, 747 adult pulmonary patients with tuberculosis who were screened for HIV and nutritional status were followed for survival. RESULTS: Of 747 patients, 310 had baseline wasting by BMI (kg/m2) and 103 by LMI (kg/m2). Total deaths were 105. Among men with reduced BMI, risk of death was 70% greater (hazard ratio [HR] 1.7, 95% confidence interval [95% CI] 1.03–2.81) than in men with normal BMI. Survival did not differ by LMI among men (HR 1.1; 95% CI 0.5–2.9). In women, both the BMI and LMI were associated with survival. Among women with reduced BMI, risk of death was 80% greater (HR 1.8; 95% CI 0.9–3.5) than in women with normal BMI; risk of death was 5-fold greater (HR 5.0; 95% CI 1.6–15.9) for women with low LMI compared with women with normal LMI. CONCLUSIONS: Wasting assessed by reduced BMI is associated with an increased risk for death among both men and women whereas reduced LMI is among women with tuberculosis.
Keywords: Tuberculosis; Survival; Wasting; Lean Tissue Mass Index; Body Mass Index; Bioelectrical Impedance Analysis.